The German Contribution to the Military History of South Africa and South-West Africa - Botha, H.J.; Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2012)
The Republic of South Africa is the spiritual. Cullural, econolll;c and military extension of the Occident on the Southern extremity of Africa.Situated where it is it does not only form an invaluable link between the East and the West, but at the same time it is one of the most important approaches to the Southern part of the African continent. The foundation of the white society at the Cape was laid by representatives from various Western European nations. In the course of time each one of them contributed towards the development of a young, vigorous nation in this vast land under the Southern Cross - a nation which since its birth, has always recognised the guidance of the Almighty God.